Brexit, Erewhon, and Utopia. Issue 2 (1st June 2021) - Fermanis, Porscha
Abstract: Viewing Brexit as part of a longer history of Anglo-Saxon racial and cultural exceptionalism, this article reflects on what Samuel Butler's satirical novel Erewhon, or Over the Range (1872) can tell us about the utopian impulses informing Brexit's neoimperialist ideology and hence about British identity politics today. Set in an inward-looking, socially homogeneous, and postindustrial society somewhere in the colonial southern hemisphere, Erewhon provides an anachronistic simulacrum of both an isolationist "Little England" and an imperial "Global Britain, " critiquing the idea of the self-sufficient, ethnonationalist "island nation" by demonstrating the extent to which it relies on the racial logic of White utopianism, as well as on a disavowal of the non-British labor that supports and sustains it.